Soil microbial communities associated with forest root diseases and Rocky Mountain forests - Lalande, Bradley, author; Stewart, Jane, advisor; Stromberger, Mary, committee member; Tinkham, Wade, committee member; Trivedi, Pankaj, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: forest inventory and analysis; soils microbes; Rocky Mountains; Armillaria